2021
DOI: 10.36233/0507-4088-72
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the spread of the SARS-CoV-2 (Coronaviridae: Coronavirinae: Betacoronavirus; Sarbecovirus) variants in the Moscow region using targeted high-throughput sequencing

Abstract: Introduction. Since the outbreak of the COVID-19 pandemic caused by SARS-CoV-2 novel coronavirus, the international community has been concerned about the emergence of mutations altering some biological properties of the pathogen like increasing its infectivity or virulence. Particularly, since the end of 2020, several variants of concern have been identified around the world, including Alpha (B.1.1.7), Beta (B.1.351), Gamma (P.1), and Delta (B.1.617.2). However, the existing mechanism of detecting important m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The use of this kit in practice has made it possible to drastically reduce the number of samples submitted for whole-genome sequencing in order to identify and monitor strains containing the S:N501Y mutation [ 15 ]. However, the further emergence of strains characterized by the appearance of additional mutations in the S-protein gene showed that genomic substitutions at the sites of LAMP primers can reduce the effectiveness of this technique [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of this kit in practice has made it possible to drastically reduce the number of samples submitted for whole-genome sequencing in order to identify and monitor strains containing the S:N501Y mutation [ 15 ]. However, the further emergence of strains characterized by the appearance of additional mutations in the S-protein gene showed that genomic substitutions at the sites of LAMP primers can reduce the effectiveness of this technique [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fast spread of Delta may be associated with its reduced sensitivity to neutralization by antibodies [ 10 ] as well as increased efficiency of fusion with human cells [ 11 ]. Delta has spread rapidly in Russia, increasing in frequency from 1% in April to over 90% in June [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…2021b ). Delta has spread rapidly in Russia, increasing in frequency from 1 per cent in April to over 90 per cent in June ( Borisova et al. 2021 ; Knorre et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%